The Correlation of Social Media, Influencers, and Brand Awareness of Y.O.U Products on Purchase Intention at Murni Stores - Pika, Putu Ayu Titha Paramita; Suari, Ni Made Mirah; Korry, Putu Dyah Permatha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The purpose of this study is to examine the influence of social media marketing, influencer marketing, and brand awareness on consumers’ purchase intention toward Y.O.U products at the Murni Store. This research applies a quantitative approach, with data collected through observation, documentation, and questionnaires. A total of 170 respondents were involved in the study, and the data obtained were analyzed using multiple linear regression analysis, the coefficient of determination, and t-tests.The results indicate that influencer marketing has a positive and significant effect on purchase intention toward Y.O.U products at the Murni Store. This is reflected in a regression coefficient of 0.269, which implies that an increase in influencer marketing activities leads to a higher level of consumer purchase intention. The t-test results support this finding, with a t-value of 3.783 and a significance value of 0.000, which is below the 0.05 significance level. These findings confirm that influencer marketing plays an important role in shaping consumer attitudes and encouraging purchasing decisions. Furthermore, brand awareness is also found to have a positive and significant influence on purchase intention. The regression coefficient of 0.107 indicates that higher brand awareness increases consumers’ interest in purchasing Y.O.U products at the Murni Store. This effect is supported by the t-test results, which show a t-value of 2.042 and a significance value of 0.043, lower than 0.05. Overall, the study concludes that influencer marketing and brand awareness are key determinants of purchase intention, highlighting the importance of effective marketing strategies in increasing consumer engagement levels.